A year in the salt marsh: Seasonal changes in gill protein expression in the temperate intertidal mussel Geukensia demissa. (October 2020) - Fields, Peter A.; Eraso, Ariel
Abstract: Organisms living in temperate and polar regions experience extensive seasonal changes in the physical and biotic environment, including temperature, insolation, and food availability, among other factors. Sessile intertidal organisms respond to such seasonal fluctuations largely through physiological and biochemical means, because their behavioral responses are severely limited. In this study, we used a proteomic approach to examine changes in seasonal protein expression of gill from the intertidal mussel Geukensia demissa, a keystone species of the western Atlantic salt marsh, over the course of one year. Gill tissue of mussels collected in summer had the greatest number of proteins significantly increased in abundance (37 of 592 spots detected on two-dimensional polyacrylamide gels), although autumn mussels revealed a comparable proportion of up-regulated proteins (31 spots). In contrast, the number of proteins changing in abundance in winter and spring mussels were substantially smaller (15 and 9, respectively). Identification of these proteins revealed both expected and unanticipated changes to the proteome. Maintenance of gill cilia dominates in the summer when filter-feeding is most active, as evidenced by cytoskeletal proteins such as tektin-4 and tubulin isoforms; a signal of protection from heat stress is also present in summer (e.g., heat shock cognate 70). In autumn oxidative stress protection (peroxiredoxin-5 and manganese-containing superoxide dismutase) and aerobic ATP synthetic capacity (ATP synthase subunits a and delta) appear to increase. In winter a signal of cold-induced oxidative stress is apparent (Mn-SOD and NADP-dependent isocitrate dehydrogenase), perhaps in association with heavy metal toxicity and exposure to pathogens. Gill tissue from spring shows relatively little environmental acclimatization, other than a possible increase in protein synthesis capacity. Highlights: Mussel gill tissue substantially alters protein expression across seasons. In summer, gill tissue optimizes ciliary function and protection against heat stress. Autumn gill maintains aerobic energy production and oxidative stress protection. Protein expression in winter suggests exposure to heavy metals.